MOTIVASI BERWIRAUSAHA BAGI REMAJA MELALUI PELATIHAN MEMBUAT CIRENG ISI SEBAGAI BISNIS RUMAHAN - Sasti Ani; Rinda Siaga Pangestuti; Tri Elsa Susilawati (Universitas Islam 45 Bekasi, 2022)
The results of observations made in Kampung Selang Tengah RT002/RW002, Wanasari sub-district, Cibitung sub-district, it turns out that there are still many teenagers, most of whom fall into the category of unemployed. This happened because at the time of this pandemic the economic sector experienced a very severe downturn, even a lot of workers were forced to be temporarily laid off or even laid off because conditions did not allow this, which in turn worsened the economic situation for the lower middle class. At times like this motivate entrepreneurship for unemployed youth, what can be done. By holding the training, it is hoped that it can motivate them to start entrepreneurship with training on making cireng content which was attended by 6 participants and bookkeeping methods through an application on a cellphone which was attended by 20 participants. Starting entrepreneurship can be a way out to earn income and can be a good impact for unemployed people starting entrepreneurship. The post test results of small businesses after doing this training showed good feedback or a very good response.